Unemployment’s Life-Satisfaction Cost and Loneliness - Friehe, Tim; Pfeifer, Christian (Journal of happiness studies, 2025)
Unemployment consistently lowers life satisfaction on average, yet the individual impact of job loss varies significantly. The underlying factors driving this heterogeneity remain a subject of ongoing research. Using data from the German Socio-Economic Panel, we demonstrate a compelling link between unemployment and loneliness, suggesting that a substantial portion of unemployment’s detrimental impact on life satisfaction can be attributed to the social isolation it induces. This finding is robust across various estimation methods and subsamples. Notably, the indirect effect of unemployment on life satisfaction through loneliness is particularly pronounced among college graduates, while it is less sizable for East Germans. Our results underscore the potential effectiveness of policies aimed at combating loneliness in mitigating the psychological well-being of the unemployed.